2020
DOI: 10.1021/acs.langmuir.0c01916
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light Intensity on the Aggregation Behavior of Primary Particles during In Situ Photochemical Synthesis of Gold/Polymer Nanocomposites

Abstract: Metal/polymer nanocomposites have attracted much attention in recent years due to their exceptional properties and wide range of potential applications. A key challenge to obtain these materials is to stabilize the metal nanoparticles in the matrix, avoiding uncontrolled aggregation processes driven by the high surface free energy of nanosized particles. Here, we investigate the aggregation mechanism of primary particles in gold−epoxy nanocomposites prepared via light-assisted in situ synthesis, under differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“… 3 , 20 This is of great interest and was recently actively explored also in the case of non silicatic fillers. 21 , 22 When dealing with sol–gel chemistry, if the reaction rates are comparable, an interpenetrating network may also be obtained from the simultaneous reactions of the organic monomer and the sol–gel precursor. 20 In addition, the sol–gel route offers the formation of an inorganic phase starting from simple low-molecular-weight precursors, allowing a nanolevel molecular design of the final structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 20 This is of great interest and was recently actively explored also in the case of non silicatic fillers. 21 , 22 When dealing with sol–gel chemistry, if the reaction rates are comparable, an interpenetrating network may also be obtained from the simultaneous reactions of the organic monomer and the sol–gel precursor. 20 In addition, the sol–gel route offers the formation of an inorganic phase starting from simple low-molecular-weight precursors, allowing a nanolevel molecular design of the final structure.…”
Section: Introductionmentioning
confidence: 99%
“…Very often, unprecedented materials were produced whose properties are not simply a combination of the two components alone . A common way to develop these materials is the use of the sol–gel synthesis route. The mild synthesis conditions in the sol–gel process allow generating an inorganic phase in the presence of the monomer or the polymer through the so-called “ in situ ” process, in which both phases are formed successively in one procedure. , This is of great interest and was recently actively explored also in the case of non silicatic fillers. , When dealing with sol–gel chemistry, if the reaction rates are comparable, an interpenetrating network may also be obtained from the simultaneous reactions of the organic monomer and the sol–gel precursor . In addition, the sol–gel route offers the formation of an inorganic phase starting from simple low-molecular-weight precursors, allowing a nanolevel molecular design of the final structure.…”
Section: Introductionmentioning
confidence: 99%
“…AuNP size increase and coalescence were initially expected due to the thermal nature of the reaction, but the minimal size increase and notable particle stabilization in the materials were unexpected results. Typically, in situ polymerizations (thermal or otherwise) with gold nanoparticles are expected to favor agglomeration and particle coalescence, so the preservation on individual nanoparticle shape and absorption properties are notable advantages to utilizing an oleylamine-functionalized AuNP surface. , …”
Section: Resultsmentioning
confidence: 99%
“…One of the most straightforward ways to facilitate a phase change within a system is through a chemical reaction. Under specific conditions, chemical reactions proceed rapidly and with triggers such as temperature, light, and mechanical activation . An example of a reaction-induced phase transition (RIPT) is frontal polymerization .…”
Section: Introductionmentioning
confidence: 99%
“…As an important engineering material, epoxy resin (EP) is widely used in adhesives, electronic packaging materials, aerospace, building materials, chemical anticorrosion, and other fields. However, there are two major challenges that hinder the use of EP. One, EP is easy to burn and leads to major fire hazards and has massive cost for fire protection. Another challenge is that pure EP is brittle with poor friction and wear resistance. Recently, many studies have demonstrated that the combination of EP and inorganic fillers can improve the wear resistance, for example, nanofillers such as SiO 2 , Al 2 O 3 , graphene, hexagonal boron nitride (h-BN), and carbon nanotubes , can significantly improve the wear resistance and mechanical strength of EP.…”
Section: Introductionmentioning
confidence: 99%